TASS upolnomochen zaiavit' 1-2 - Fokin, Vladimir (Soviet Union : Gosteleradio SSSR, 1984)
A spy is sent to Moscow. Soviet intelligence is trying to neutralize him and thus prevent a revolt, prepared by the CIA, in the fictional third-world state of Nagonia.
Keywords: Fiction films